Studies on the antimicrobial activity and brine shrimp toxicity of Zeyheria tuberculosa (Vell.) Bur. (Bignoniaceae) extracts and their main constituents - Rocha Eliana MM; Andrade Vânia S; Conserva Lucia M; Lima Maria; Bastos Maria; Lemos Rosangela PL (BMC, 2009)
Abstract Background Due to the indiscriminate use of antimicrobial drugs, the emergence of human pathogenic microorganisms resistant to major classes of antibiotics has been increased and has caused many clinical problems in the treatment of infectious diseases. Thus, the aim of this study was to evaluate for the first time the in vitro antimicrobial activity and brine shrimp lethality of extracts and isolated compounds from Zeyheria tuberculosa (Vell.) Bur., a species used in Brazilian folk medicine for treatment of cancer and skin diseases. Methods Using the disc diffusion method, bioautography assay and brine shrimp toxicity test (Artemia salina Leach), we studied the antimicrobial activity and lethality of extracts and isolated compounds against three microorganisms strains, including Gram-positive (Staphylococcus aureus) and Gram-negative (Pseudomonas aeruginosa) bacteria and yeasts (Candida albicans). Results In this study, the extracts inhibited S. aureus (8.0 ± 0.0 to 14.0 ± 0.0 mm) and C. albicans (15.3 ± 0.68 to 25.6 ± 0.4 mm) growth. In the brine shrimp test, only two of them showed toxic effects (LC50 29.55 to 398.05 μg/mL) and some extracts were non-toxic or showed weak lethality (LC50 705.02 to > 1000 μg/mL). From these extracts, four flavones [5,6,7,8-tetramethoxyflavone (1), 5,6,7-trimethoxyflavone (2), 4'-hydroxy-5,6,7,8-tetramethoxyflavone (3), and 4'-hydroxy-5,6,7-trimethoxyflavone (4)] were isolated through bioassay-guided fractionation and identified based on the 1D and 2D NMR spectral data. By bioautography assays, compounds 1 [S. aureus (16.0 ± 0.0 mm) and C. albicans (20.0 ± 0.0 mm)] and 3 [S. aureus (10.3 ± 0.6 mm) and C. albicans (19.7 ± 0.6 mm)] inhibited both microorganisms while 2 inhibited only S. aureus (11.7 ± 0.6 mm). Compound 4 did not restrain the growth of any tested microorganism. Conclusion Our results showed that extracts and isolated flavones from Z. tuberculosa may be particularly useful against two pathogenic microorganisms, S. aureus and C. albicans. These results may justify the popular use this species since some fractions tested had antimicrobial activity and others showed significant toxic effects on brine shrimps. However, in order to evaluate possible clinical application in therapy of infectious diseases, further studies about the safety and toxicity of isolated compounds are needed.